Formulation of Red Spinach and Celery Jelly Candy as Functional Food Innovation and Stunting Prevention - Merba, Brigita Lestari; Payung, Estherina Allo; Purnaningrum, Gabriella Natalika; Tangka, Triyani Rinfiana; Kurniawan, Kaleb (Gema Wiralodra, 2025)
Stunting is a child growth disorder due to unmet nutritional requirements (RDA) starting from the growth period in the foetus until the age of 2 years. Functional food innovation, jelly candy, is an alternative to prevent stunting and supports the effective use of natural ingredients, such as red spinach and celery. The purpose of this study was to analyse the best formula of red spinach and celery as raw materials for jelly candy and its effectiveness for stunting prevention. The research method is experimental jelly candy formula with 3 variations of raw material concentration, namely F1 (10:0.7), F2 (12:0.78), and F3 (14:0.86), and analysing formula variations with several analytical methods, namely vitamin C and iron tests using iodimetric and permanganometric titration methods, moisture content test using gravoimetric method, pH test using pH meter, and organoleptic test. The results of the research analysis showed that the physical and chemical characteristics of the formula met the quality standards of jelly candy. The physical characteristics of each formula showed normal colour and scent, chewy texture, sweet taste, moisture content ≥ 20%, and pH 7. The chemical characteristic showed that the higher the concentration of spinach and celery leaves, the higher the levels of vitamin C and iron content. The vitamin C content F1 = 11; F2 = 18; F3 = 22mg, and iron content F1 = 26; F2 = 34; F3 = 26mg. Based on the results obtained, it is concluded that F2 is the best formula effective formula used to prevent stunting by fulfilling the RDA for pregnant women and toddlers.